Paleomagnetism of Mesozoic plutons in the westernmost Coast Complex of British Columbia - Symons, D. T. A. (Canadian Journal of Earth Sciences, 1977)
The Lower Cretaceous Stephens Island (102 ± 8 Ma) and Captain Cove (109 ± 6 Ma) plutons and the Upper Jurassic Gil Island (136 ± 3 Ma) and Banks Island (144 ± 6 Ma) plutons belong to the western K–Ar age zone of the N 35° W trending Coast plutonic complex southwest of Prince Rupert, B.C. After removal of initial viscous components, AF demagnetization isolates a stable primary remanence at 36 of 49 sites (10 specimens from 5 cores/site) before anhysteretic components are added. All sites have normal polarity which is consistent because their K–Ar ages fall in the predominantly normal Cretaceous and Jurassic Quiet Intervals. The poles for Stephens Island (339° W, 67° N (7°, 10°)), Captain Cove (9° W 72° N (8°, 11°)), and Gil Island (357° N. 70° N (6°, 8°)) lie just north of Britain and are discordant for the North American craton. The tectonic panel including these plutons was tilted [Formula: see text] during the Upper Cretaceous–Paleocene orogeny as the leading edge of the North American plate overrode the subducting oceanic Kula Plate. This interpretation is supported by other arguments including the attitudes of contacts and foliations, plutonic trend directions, distribution of metamorphic grades, and paleomagnetic data from the area to the east. The Banks Island pluton lies in the tectonic panel to the west. Its pole of 210° W, 81° N (33°, 38°) is poorly defined but apparently concordant.